Relaciones endodóntico-protésicas, postes y muñones - Gerardo Becerra-S; Guillermo L. Valencia-R (Universidad de Antioquia, 1998)
Custom- cast posts and cores or prefabricated intrarradicular posts that retain a plastic material are often necessary ivben there is an inadequate coronal tooth structure to support a restoration. Some studies have reported that design, length and type of the endodontic post will influence the prognosis of the restorations. The aim of this article IS to establish some considerations and a classification srstem for the intrarad/cular elements.